2000
DOI: 10.1080/07481180050132811
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Professionals' Training and Experiences in Delivering Death Notifications

Abstract: A mail survey was conducted of 240 people from different professions that routinely encountered death to assess their previous training and experiences in delivering death notifications. Nearly 40% of these persons had received neither classroom nor experiential training in death notification, although 70% of respondents had performed at least one notification. The causes of death that contributed to notifiers' distress during notification included (a) violent crime, (b) drunk driving crashes, (c) suicide, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…The second objective was to examine the effects of police behavior on mental health (prolonged grief, depression, PTSD) of the bereaved. The present study partially replicates previous findings by showing effects of perceived negative behaviors of police officers on the outcomes mentioned above (Baumann & Stark, 2015;Parris, 2011;Roe, 2012;Stewart et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The second objective was to examine the effects of police behavior on mental health (prolonged grief, depression, PTSD) of the bereaved. The present study partially replicates previous findings by showing effects of perceived negative behaviors of police officers on the outcomes mentioned above (Baumann & Stark, 2015;Parris, 2011;Roe, 2012;Stewart et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Beside these findings, Stewart et al (2000) showed that the person delivering the death notification is often insecure about dealing with these reactions and, therefore, cannot provide adequate support. As a result, bereaved relatives often feel left alone in a situation that already seems unbearable.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 19 studies ( Table 2 ) described the notification process, taking into account both perspectives. From the notifier's point of view, the notification process is mostly judged as difficult and stressful (Adamowski et al, 1993 ; Stewart et al, 2000 ; Janzen et al, 2003-2004 ; Hart and DeBernardo, 2004 ; Douglas et al, 2012 ; Williams-Reade et al, 2018 ). The reactions most commonly described by the notifier are: anxiety, guilt, sadness, identification with the target, discomfort, avoidance, anguish, frustration, isolation, insomnia, lowering of mood, recurrent nightmares, feelings of helplessness, substance abuse, marital conflict, PTSD, chronic stress response syndrome, and professional burnout (Spencer et al, 1987 ; Veilleux and Bilsky, 2016 ; Tuffrey-Wijne and Rose, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Delivering death notifications is one of the most disliked tasks in the police profession, which many police officers would rather avoid. Delivering a death notification can have a lasting impact not only on the bereaved relatives, but also on the persons delivering the message, such as the police officers (24)(25)(26). Studies have shown that in the aftermath the persons delivering the messages often suffer from sadness, insomnia, feelings of helplessness, fear, and guilt (27).…”
Section: Introductionmentioning
confidence: 99%